Hypertension combined with limitations in activities of daily living and the risk for cardiovascular disease - Yiqun Li; Minglan Jiang; Xiao Ren; Longyang Han; Xiaowei Zheng; Wenyan Wu (BMC Geriatrics, 2024)
Abstract Objective The aim of present study was to evaluate the combined effect of hypertension and activities of daily living (ADL)/instrumental activities of daily living (IADL) with the risk of CVD, stroke and cardiac events. Methods A total of 14,083 participants aged 45 years or older from the China Health and Retirement longitudinal study were included in current study. Participants were divided into 4 groups according to hypertension and ADL/IADL status. Cox proportional hazards regression model was used to explore the associations between hypertension, ADL/IADL and new-onset CVD, stroke and cardiac events. Results During the 7-year follow-up, a total of 2,324 respondents experienced CVD (including 783 stroke and 1,740 cardiac events). Individuals with limitations in ADL alone, or with hypertension alone, or with both limitations in ADL and hypertension were associated with increased risk of CVD, with the adjusted hazard ratios (95% confidence intervals) were 1.17(1.00-1.35), 1.36(1.24–1.49) and 1.44(1.23–1.68), respectively. Those with limitations in ADL and hypertension also had higher risk of stroke (hazard ratios = 1.64; 1.26–2.14) and cardiac events (hazard ratios = 1.37; 1.14–1.64). Similarly, individuals with both limitations in IADL and hypertension were associated with increased risk of CVD (hazard ratios = 1.34; 1.15–1.57), stroke (hazard ratios = 1.50; 1.17–1.95) and cardiac events (hazard ratios = 1.27; 1.06–1.53). Conclusion Hypertension and limitations in ADL/IADL jointly increased the risk of CVD, stroke and cardiac events.